Producing Liquid Fuels from Coal Prospects and Policy Issues - Bartis, James T. (RAND Corporation, 2008)
Large U.S. coal reserves and viable technology make promising a domesticindustry producing liquid fuels from coal. Weighing benefits, costs, andenvironmental issues, a productive and robust U.S. strategy is to promote alimited amount of early commercial experience in coal-to-liquids productionand to prepare the foundation for managing associated greenhouse-gasemissions, both in a way that reduces uncertainties and builds futurecapabilities.